Optogenetic analysis of inhibitory circuits in the neocortex - Kätzel, D (2011)
Information processing in the brain involves circuits composed of different classes of neurons. Inhibitory interneurons are by far the most diverse subgroup in terms of physiology and morphology, and the principles that govern their connectivity are far from understood. Their excitatory counterparts, pyramidal and spiny stellate cells, have been found to be governed by a compartmentalized horizontal and vertical structure – forming layers and columns – as well as by a stereotypic or “canonical” pattern of connections between them. However, it has remained unclear whether similar, general organizing principles exist for inhibitory circuits. To map the sources of inhibitory inputs to neocortical pyramidal cells, a Cre-lox-based mouse knock-in line, that conditionally expresses the light-sensitive ion channel channelrhodopsin-2 in GABAergic neurons, was generated. Expression levels were sufficient to drive interneuron spiking at up to 40 Hz, but too low to activate synaptic terminals allowing perisomatic activation and thus mapping of local connections. I found, that inhibitory inputs to excitatory cells in all layers in primary motor (M1), somatosensory (S1), and visual cortex (V1) derive largely from the same layer and putative column. However, four translaminar inhibitory connections were found, which differ significantly both, between as well as within a cortical area. Most notably, (some) excitatory cells in layers 2/3, 4 and 5B of V1 receive prominent, putative feedback inhibition from their direct or indirect output layers. Furthermore, while a columnar structure is visible also in inhibitory circuits, their laminar organization is degenerate in an area-specific manner. Neocortical inhibitory microcircuits thus display significant variations, which potentially reflect the localization of function.